A qualitative study to explore the experiences faced by primary caregivers of children with mental illness during the COVID-19 pandemic at the child and adolescent psychiatry OPD - Jyoti Gogoi; Radhakrishnan Govindan; Bingi Rajeswari; John V. S. Kommu (Indian Journal of Psychiatry)
Aim: To explore the lived-in experiences of primary caregivers of children with mental illness while taking care during the coronavirus disease 2019 (COVID-19) pandemic. Methodology: This study is a descriptive phenomenological study. Convenience sampling was used. Data were collected by in-depth interviews of 30 primary caregivers of children with mental illness, during the COVID-19 pandemic. All interviews were audio-recorded and analyzed using a thematic approach. Results: The overall aura of fear and panic brought by the pandemic found its way into the psyche of patients and the development of their illnesses during the pandemic. The entirety of the work brought out three themes and 11 subthemes as categorized for the aim of this study. Conclusion: Primary caregivers of children with mental illness during the COVID-19 pandemic reveal that lifestyle changes, such as online education, confinement, overuse of electronic gadgets, and increased laziness and lethargy in children after prolonged lockdown, were drastic changes which caregivers had to deal with.